2022
DOI: 10.1186/s13065-022-00879-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological evaluation and molecular docking of new triphenylamine-linked pyridine, thiazole and pyrazole analogues as anticancer agents

Abstract: A new series of pyridine, thiazole, and pyrazole analogues were synthesized. The pyridone analogues 4a-e were synthesized by treating N-aryl-2-cyano-3-(4-(diphenylamino)phenyl)acrylamides 3a-e with malononitrile. Many 4-arylidene-thiazolidin-5-one analogues 6a-d were obtained by Knoevenagel reactions of 4-(diphenylamino)benzaldehyde (1) with their corresponding thiazolidin-5-one derivatives 5a-d. The structural elucidation of the products was proven by the collections of spectroscopic methods such as IR, 1H NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The cancer cells were cultured in a 96‐well plate at a volume of (100 L/well), following the methods of Skehan et al . with slight modifications [31,32] . Initially, the cells were exposed to DMSO (0.5 % V/V) or 50 M of each tested chemical for an overnight incubation at 37 °C and 5 % CO2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cancer cells were cultured in a 96‐well plate at a volume of (100 L/well), following the methods of Skehan et al . with slight modifications [31,32] . Initially, the cells were exposed to DMSO (0.5 % V/V) or 50 M of each tested chemical for an overnight incubation at 37 °C and 5 % CO2.…”
Section: Methodsmentioning
confidence: 99%
“…The cancer cells were cultured in a 96-well plate at a volume of (100 L/well), following the methods of Skehan et al with slight modifications. [31,32] Initially, the cells were exposed to DMSO (0.5 % V/V) or 50 M of each tested chemical for an overnight incubation at 37 °C and 5 % CO2. After 48 h, MTT reagent (5 mg/mL in Phosphate Buffered Saline (PBS)) was added to the plate and incubated for an additional 4 h. Subsequently, formazan crystals were dissolved using a solution of acidified sodium dodecyl sulphate (SDS) (10 % SDS with 0.01 N HCl in 1× PBS).…”
Section: Biological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Likewise, breast cancer is a grave disease comprising heterogeneous tumors allied with a characteristic histological pattern and diverse clinical features. 62 In this context, the tested silver complexes are arranged and compared with the vinblastine drug in the following order: vinblastine > 3 > HGMF > 1 > 2. Interestingly, the displayed higher cytotoxicity of complex 3 via the examined cell lines may be due to its higher DNA binding affinity than the other prepared silver complexes.…”
Section: In Vitro Cytotoxicity Screeningmentioning
confidence: 99%
“…Many groups have worked on CDK2 inhibition with the help of molecular docking. For instance, (Mansour et al, 2021b, Elmorsy et al, 2022 reported novel pyridine-3carbonitrile derivatives as anticancer compounds against the CDK2 enzyme (79-82) (Fig. 19), Eldehna and his group studied three series of oxindole-benzofuran hybrids (83-85) (Eldehna et al, 2021a) (Fig.…”
Section: Cell Cycle Cyclin-dependent Kinasesmentioning
confidence: 99%